4.4-μm Raman generation with an average power above 1 W in silica revolver fibre. (December 2018) - Astapovich, M.S.; Gladyshev, A.V.; Khudyakov, M.M.; Kosolapov, A.F.; Likhachev, M.E.; Bufetov, I.A.
Abstract: We report the first gas-filled fibre Raman laser emitting at 4.42 μm with an average power of 1.4 W. Its gain medium is silica revolver fibre with a molecular hydrogen ( 1 H2 ) filled hollow core. Owing to the use of linearly polarised 1.56-μm pump light and a polarisation-maintaining Raman laser configuration, we have achieved a quantum efficiency of 53% for single-stage 1.56 → 4.42 μm conversion. This fibre Raman laser can find application in medicine, gas analysis and other areas.